Possible involvement of proteasome activity in ethyleneinduced germination of dormant sunflower embryos - Borghetti, Fabian (2012)
Freshly harvested sunflower seeds (Helianthus annuus L., Asteraceae) present physiological dormancy localized at the embrionary axis which prevents germination at low temperatures. However, dormant embryos reach about 100 % germination when incubated with the phytohormone ethylene during imbibition. To examine whether proteinase activities are implicated in the breaking of dormancy by ethylene, dormant embryos were treated with the proteinase inhibitors leupeptin, E64 and the proteasome specific inhibitor clasto-lactacystin ß-lactone (lactacystin). A few embryos (< 10 %) germinated at 10 oC in absence of ethylene but ethylene-treated embryos reached high germinability (~90 %) in the presence of leupeptin, E64, water and DMSO. On the other hand, incubation in lactacystin strongly reduced (< 20 %) the ethylene-induced germination in a dose-dependent manner. Lactacystin did not affect the germinability at 25 oC (temperature in which the embryos are no longer dormant) but increased the average germination time. The results suggest that proteasome activity may be involved in the removal of dormancy by ethylene and in the progression of the germination of sunflower embryos. _________________________________________________________________________________ ABSTRACT